KEK Law and Its Economic Implication - Salamuddin Daeng (Budapest International Research and Critics University, 2020)
This article describes implications of Indonesia government policy regarding to Special Economic Zones in Batam. The pioneer of Special Economic Zones had been exist with the enforcement of constitution about free trade and free port. Facilities or convenience is a factor that will attract investors, through this facility, it is expected investors just simply come to the concern government to take care of all permits relating to the investment activities. On the other side, facilities or incentives provided by legislation to investors, such as privileges or special treatment in certain different outside SEZ areas, that is the tax holiday for a period of time, the suspension or exemption of import duty, including tax.